Elucidating the Host Interactome of EV-A71 2C Reveals Viral Dependency Factors - Li, Ye; Jian, Xia; Yin, Peiqi; Zhu, Guofeng; Zhang, Leiliang (Frontiers in Microbiology, 2019)
Viral protein 2C plays a critical role in EV-A71 replication. The discovery of 2C binding proteins will likely provide potential targets to treat EV-A71 infection. Here, we provide a global proteomic analysis of the human proteins that interact with the EV-A71 2C protein. TRIM4, exportin2 and ARFGAP1 were validated as 2C binding partners. Further functional studies revealed that TRIM4, exportin2 and ARFGAP1 were novel host dependency factors for EV-A71. Moreover, enteroviruses 2C family proteins interacted with exportin2 and ARFGAP1. In conclusion, our study provides a cellular interactome of the EV-A71 2C and identifies the proviral roles of TRIM4, exportin2 and ARFGAP1 in EV-A71 infection.